2005
DOI: 10.1128/cdli.12.10.1168-1176.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus neoformans -Reactive and Total Immunoglobulin Profiles of Human Immunodeficiency Virus-Infected and Uninfected Ugandans

Abstract: We determined total and Cryptococcus neoformans glucuronoxylomannan (GXM)-reactive antibody repertoires of human immunodeficiency virus (HIV)-infected and HIV-uninfectedThe results showed that HIV-infected subjects had significantly lower levels of IgM to GXM but higher levels of total immunoglobulin and IgG and IgA to GXM than those of HIV-uninfected subjects. HIV-infected subjects with a history of pneumonia had higher levels, and those with a history of herpes zoster had lower levels of GXM-binding antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
44
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 70 publications
6
44
2
Order By: Relevance
“…A loss of IgM memory B cells was implicated in susceptibility to pneumococcus and impaired antibody responses to PPS (23,36,44) and in infections with encapsulated bacteria in patients with common variable immunodeficiency (6). There were no cases of pneumococcal disease in either the C. neoformans-positive or C. neoformans-negative cohort, and a previous study found no association between GXM-and PPS-reactive antibodies (40). However, the foregoing studies suggest an intriguing link to cryptococcal pathogenesis, since reduced memory IgM is a central defect in patients with increased risk for cryptococcosis, such as those with common variable immunodeficiency (2, 38), hyper-IgM (3,19,21,42), and HIV (32).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…A loss of IgM memory B cells was implicated in susceptibility to pneumococcus and impaired antibody responses to PPS (23,36,44) and in infections with encapsulated bacteria in patients with common variable immunodeficiency (6). There were no cases of pneumococcal disease in either the C. neoformans-positive or C. neoformans-negative cohort, and a previous study found no association between GXM-and PPS-reactive antibodies (40). However, the foregoing studies suggest an intriguing link to cryptococcal pathogenesis, since reduced memory IgM is a central defect in patients with increased risk for cryptococcosis, such as those with common variable immunodeficiency (2, 38), hyper-IgM (3,19,21,42), and HIV (32).…”
Section: Discussionmentioning
confidence: 83%
“…The possible roles of antibodies to GXM in resistance and susceptibility to cryptococcosis are unknown, but available data suggest that the naturally occurring GXM-reactive repertoire may contribute to resistance (discussed in references 8 and 10). Studies comparing HIV-infected and HIV-uninfected individuals, groups that are at very high and low risk for cryptococcosis, respectively, have also found lower levels of GXM-reactive IgM in HIV-infected subjects than in HIV-uninfected subjects (13,17,40), including individuals with relatively intact T-cell immunity (13). The data presented herein suggest that a reduced level of GXM-reactive IgM could portend a risk of cryptococcosis in the setting of immunosuppression, although whether it reflects previously unrecognized variation in the population or is induced by HIV infection or transplantation is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with this hypothesis, underlying B-cell defects are common in patients with hypogammaglobulinemia and hyper-immunoglobulin M (IgM) syndromes, immunoglobulin disorders that have been linked to an increased risk for cryptococcosis (discussed in reference 61). Lower levels of GXM-reactive IgM have been found among HIV-infected individuals than among HIV-uninfected individuals (61). IgM, like complement, is an important serum opsonin.…”
Section: The Microbe As An Encapsulated Pathogenmentioning
confidence: 99%